Optimasi Parameter Pemesinan Menggunakan Metode Taguchi Untuk Meningkatkan Kualitas Kebulatan Pada Pembubutan Internal Material S45C - Joko Setia Pribadi; Yulianto Yulianto; Bayu Aji Girawan (P3M Politeknik Negeri Cilacap, 2020)
The proper use of machining parameters in order to improve general quality is expected to optimize the results of the machining process including the use of the Taguchi experimental design. Several controlled parameters are carried out that are the cutting and feed speed, and cutting depth with three levels in the internal turning process of S45C steel material. Experiments were carried out using the Taguchi experimental matrix L9(34). The turning results are rounded and the variance and signal to noise ratio analysis are carried out in accordance with the proposed Taguchi design. The results obtained, the cutting speed and the identified cutting depth factors affect the roundness of the internal turning results. The results of the analysis of variance on the S/N ratio with smaller and better quality characters and based on hypothesis testing, is that the cutting speed and significant cutting depth parameters with a 90% confidence level affect roundness. The conditions of the cutting speed of 200 [m/min], the feed speed of 0.05 [mm/rev], and the cutting depth of 0.25 [mm] are the optimum parameters obtained.